1933 Haw. Sess. Laws 38-39 - (:unkn) unknown (My University, 1933)
An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, § 7: Prohibited the manufacture, possession, sale, barter, trade, gift, transfer, or acquisition of any machine guns, automatic rifles, cannon, mufflers, silencers, or devices for deadening or muffling the discharge of a firearm, or any bomb, or bombshell. Violators fined not more than one thousand dollars, or imprisoned for one year, or both fine and imprisonment.
Keywords: FIREARMS COMMONLY USED FOR CRIME; MACHINE GUN RESTRICTION